A mulher na transição menopausal: autopercepção das mudanças físicas, emocionais e sociais - Busetti, Karen Priscila Pereira (2020)
Introduction: The menopausal transition is a physiological phase of a woman's life, between the reproductive period and the menopause. The clinical picture comprises hot flushes, genitourinary symptoms, sleep disorders, depression. It does not correspond only to a physiological phenomenon of follicular exhaustion caused by progressive hypoestrogenism. Moreover, its perception will be influenced by political, economic, behavioral, socio-cultural and environmental factors. Prior knowledge about what happens during the menopausal transition and after menopause, as well as the practice of healthy living can reduce symptoms and modulate the way women face this phase. Objective: We sought to evaluate the self-perception of the symptoms of the menopausal and post-menopausal transition of health professionals and how it affects their lives, in the physical, emotional, interpersonal relationships, social, work and cultural behavior. Method: a cross-sectional quantitative and qualitative study that assessed the subjective perception of this stage of life and symptoms. The research subjects were a group of employees from the nursing / administrative sector of the Conjunto Hospitalar de Sorocaba in the menopausal transition and in the postmenopause. The research was approved by the Comitê de Ética e Pesquisa da Faculdade de Ciências Médicas e da Saúde da PUC / SP, the research instrument was developed and validated (semi-structured questionnaire). This work included 24 subjects who met inclusion criteria getting care and gynecological monitoring of nursing professionals. Individual interviews were recorded and later transcribed. From the material obtained through answered questionnaires, the methodological strategy of the Discourse of the Collective Subject was chosen, which was the reference as an instrument for organizing and analyzing the interviews and qualitative questions. Results: The profile of the patients was compatible with climacteric conditions, the themes detected in the referred speeches were distributed as follows: (1) selfperception of symptoms;(2) the influence of personal, family, social and professional relationships;(3) expectations regarding Health and Health Education strategies. Conclusion: We found a high rate of comorbidities in this population (95.8%); in the emotional sphere there was a fear of aging accompanied by the feeling of embarrassment of the symptoms, there was also a feeling of loss of femininity. Despite the participants in this series were health professionals, their speeches and positions did not differ from what the authors describe for the general population